Perancangan Sistem Backend Real-Time Berbasis FastAPI dan Firebase Untuk Klasifikasi Sampah Bahan Berbahaya dan Beracun Serta Pengambilan Lokasi Dropbox Pada Aplikasi Mobile TOXMAP - Gading Aurelia Nabila Lubis; Rita Purnamasari; Khaerudin Saleh (eProceedings of Engineering, 2025)
Hazardous household waste (B3) poses serious risks to the environment and public health when improperly managed. To address this, TOXMAP was developed as a mobile-based system that combines real-time image classification with location-based waste disposal guidance. This study presents the backend development of TOXMAP, which integrates a FastAPI server to process image inputs and classify waste types using a pre-trained Support Vector Machine (SVM) model. Firebase services support user authentication, image storage, and dropbox location retrieval. To complement this backend, the TOXMAP frontend was built using Flutter, enabling cross-platform mobile deployment with support for camera access and real-time image submission. Integration and load testing show that the system can respond in under one second per request while maintaining classification accuracy and user responsiveness. This architecture offers a lightweight, scalable, and user-accessible infrastructure to promote public awareness and responsible household B3 waste management.Keywords— backend, real-time system, image classification, FastAPI, Firebase, B3 waste